WOMEN'S STRATEGIES IN LONG-DISTANCE MARRIAGE: COMMUNICATION AND PARENTING - Hasanah, Uswatun; Hasanah, Ida Faridatul; Wianti, Nur Isiyana; Ningrum, Ayu Reza (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Long Distance Marriage (LDM) is increasingly common in the era of globalization but poses complex challenges for couples. This study explores women’s adaptive strategies, focusing on communication and parenting dynamics in the context of LDM families. Using a qualitative case study approach with seven families in Gunung Pelindung District, East Lampung, this study uncovers collaborative strategies for maintaining family harmony. The research findings show that women develop innovative approaches to maintaining emotional bonds with their spouse and children, including regular communication scheduling, flexible role allocation, self-care, community support, creatively educating children, and using technology to stay connected. It can be concluded that the success of long-distance marriages relies on effective communication, mutual support, and a shared adaptive strategy. Implications of the study include a deeper understanding of contemporary family dynamics in the context of global mobility.